2018
DOI: 10.17537/2018.13.270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Harvest on the Dynamics of Populations with Age and Sex Structures

Abstract: The paper investigates influence of sex- and age-specific harvest on the dynamics of structured populations based on the mathematical model with discrete time. We assume birth rate depends on the population sex ratio and is described by the modified harmonic mating function with switching. The population size is regulated by decreasing juvenile survival rate with growth of sex-age class sizes. The aim is to study the mechanisms of formation and evolution of dynamic modes for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…However, this approach makes it possible to study and take into account the possibility of changing the dynamic mode in an exploited population. In particular, it was shown that, for an exploited two-age population (both with and without sex structure), it remains possible to implement various dynamic modes at the same population parameter values depending on the initial abundance, which is characteristic of a freely developing population (Neverova et al, , 2017(Neverova et al, , 2018Revutskaya et al, 2018). Therefore, to stabilize the dynamics, the current population size should be "retained" in the basin of attraction of the mode of interest (for example, by reducing the abundance of one of the age and sex classes).…”
Section: Changing the Dynamic Modes In Populations: Influence Of Modimentioning
confidence: 99%
“…However, this approach makes it possible to study and take into account the possibility of changing the dynamic mode in an exploited population. In particular, it was shown that, for an exploited two-age population (both with and without sex structure), it remains possible to implement various dynamic modes at the same population parameter values depending on the initial abundance, which is characteristic of a freely developing population (Neverova et al, , 2017(Neverova et al, , 2018Revutskaya et al, 2018). Therefore, to stabilize the dynamics, the current population size should be "retained" in the basin of attraction of the mode of interest (for example, by reducing the abundance of one of the age and sex classes).…”
Section: Changing the Dynamic Modes In Populations: Influence Of Modimentioning
confidence: 99%
“…f < hm) увеличение доли изъятия самок и самцов не приведет к изменению соотношения полов. Такое поведение системы типично и для случая, когда промыслу подвергались только самки репродуктивного возраста [17].…”
Section: заключениеunclassified
“…Данная работа развивает предшествующие авторские исследования [17] и посвящена изучению влияния избирательного промысла самок и самцов репродуктивного возраста на динамику численности популяции с половой и возрастной структурами методами математического моделирования. Предполагается, что при промысле добываются самки и самцы репродуктивного возраста с одинаковой интенсивностью.…”
Section: Introductionunclassified
“…For example, the commercial value of sturgeon, whitefish, and salmon varies depending on their age [1]. Note that the consequences of age-specific or stage-specific harvesting have been extensively investigated [2][3][4][5][6][7][8][9][10][11][12], while the impact of harvesting individuals of different sexes on population dynamics has been less studied [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%